Influence Perceived Usefulness, Perceived Ease of Use, Attitude dan Behavioral Intention Terhadap Customer Satisfaction: Study on Application Users PLN Mobile in PT PLN (Persero) UP3 Rantauprapat - Windy Novalina Marpaung (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2026)
This study aims to analyze the influenceperceived usefulness,perceived ease of use,attitude, Andbehavioral intentiontocustomer satisfactionon PLN Mobile application users at PT PLN (Persero) UP3 Rantauprapat. The study used a quantitative approach with a causal associative design. The research sample consisted of 390 respondents selected through a purposive sampling technique. Data collection was conducted using a questionnaire with a Likert scale, while data analysis used multiple linear regression with the help of SPSS version 24. The results showed that the four independent variables, namelyperceived usefulness,perceived ease of use,attitude, Andbehavioral intention, has a positive and significant effect oncustomer satisfaction, both partially and simultaneously. These findings indicate that perceived usefulness, ease of use, positive attitudes, and users' continued intention to utilize the PLN Mobile application can increase customer satisfaction levels. The implications of this study emphasize the importance of PT PLN (Persero) continuing to strengthen the application's quality by improving features, ease of navigation, and user experience to maintain customer satisfaction and loyalty in the era of digitalized public services.